Analysis of Polycyclic Aromatic Hydrocarbons (PAHs) in Household Dusts of the City of Khorramabad, Iran - N. Dalvand; S. Sobhan Ardakani; M. Kiani Sadr; M. Cheraghi; B. Lorestani (علوم آب و خاک, 2022)
Individuals spend a lot of time indoors, thus they can generally be exposed to polycyclic aromatic hydrocarbons (PAHs) as a teratogen, mutagen, and carcinogen pollutants with the potential for environmental and also human health risks. Therefore, the current study was performed to analyze PAHs in household dust samples of the city of Khorramabad, Iran in 2019. A total of 50 indoor dust samples were collected from 10 sampling sites. After the extraction of analytes, the gas chromatography/mass spectrometry (GC–MS) method was used to determine PAHs in the studied samples. All statistical analyses were performed by SPSS software. The results showed that 16 priority PAHs were detected in the samples with the minimum, maximum, and mean values of 14.0, 23.3, and 19.2 µg/kg. Also, based on the results the mean contents of detected PAHs were lower than the maximum permissible concentration (MPC) established by MHWS and Iran DOE. In conclusion, due to exposure risks of PAHs, regular and periodic analysis of these pollutants in different environmental samples including soil, sediment, dust, particulate matter, air, water, and tissues of living organisms for environmental and human health maintenance is recommended.